Sustainable Biohydrogen Production from Palm Oil Mill Effluent: Effect of Hydraulic Retention Time in a Hybrid Anaerobic System - Ahmad, Adrianto; Evelyn, Evelyn; Andrio, David; Avriliani, Dini; Dalil, M.; Hamzah, Amir (Leuser Journal of Environmental Studies, 2026)
Currently, the world is facing two crises: a shortage of fossil fuels and global climate change. Climate change is linked to increased environmental damage from fossil fuel use and the effects of greenhouse gases. Therefore, it is important to achieve breakthroughs to develop alternative energy sources that can replace fossil fuels. One of these is biohydrogen, which plays an important role in future energy because it is environmentally friendly, renewable, and sustainable. In addition, Indonesia is the world's largest producer of palm oil, which naturally generates liquid waste. Using palm oil mill liquid waste to produce biohydrogen via an anaerobic hybrid bioreactor during the acidogenesis phase is the best solution to address environmental impacts while simultaneously providing a clean energy source. This research aims to produce biohydrogen from palm oil mill liquid waste. This was done using an anaerobic hybrid bioreactor during the acidogenesis phase, with hydraulic retention times of 6, 12, and 18 hours. The research results show that the best hydraulic retention time is 18 hours, with a VSS removal efficiency of 98% and biogas production of 5.0 L/day, yielding 64% biohydrogen.